Content Marketing TikTok dan Keputusan Pembelian Kosmetik Wardah - Fitri isnaini Fausia; Muh Syarif (Management Department of Economics and Business Of Trunojoyo Madura University, 2026)
This study aims to analyze the influence of TikTok content marketing on purchasing decisions for Wardah cosmetic products among Generation Z students at the Faculty of Economics and Business, Universitas Trunojoyo Madura. Content marketing in this study consists of four main elements, namely visual, audio, caption, and review. This research uses a quantitative approach with a survey method by distributing questionnaires to respondents who meet the research criteria. The sampling technique used purposive sampling. The collected data were analyzed using multiple linear regression analysis with the assistance of IBM SPSS software. The results show that simultaneously the variables of visual, audio, caption, and review in TikTok content have a significant influence on purchasing decisions for Wardah cosmetic products. Partially, the visual and review variables have a significant effect on purchasing decisions, while the audio and caption variables do not have a significant effect. These findings indicate that attractive visual elements and user reviews are important factors influencing Generation Z consumers in making purchasing decisions for cosmetic products.